The key of green - Smith, Bruce R. (University of Chicago Press, 2009)
A unique cultural history, 'The Key of Green' considers the significance of the colour in the literature, visual arts, and popular culture of early modern England. Contending that colour is a matter of both sensation and emotion, the author examines Renaissance material culture as well as music, theatre and philosophy.
10.7208/chicago/9780226763811.001.0001/upso-9780226763781
Keywords: Englisch; Literatur; Farbe; Visuelle Wahrnehmung; Sinne; English literature; Color in literature; Color; Color (Philosophy); Visual perception in literature; Senses and sensation in literature; Mind and body in literature